Mother-Child Communication Pattern on Awe-Awe Doer Family: A Study in Kalibaru Manis Village Banyuwangi Regency - Senny Weyara Dienda Saputri; Khutobah Khutobah; Dwi Risqiana (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
This research focused on describing communication pattern between mother and her young child in awe-awe doer family. The study held in Kalibaru Manis village in Banyuwangi regency, Indonesia, with descriptive qualitative methodology. There’re three mothers participated as informants, all of them are awe-awe doer and likely to bring their children when working on the street. The result shows that there are protective communication pattern in mother-young children relationship, with varied level of controlling behaviour and disciplinary techniques used in the family that depend on the importance of discipline and level of the mother’s confidence to assert discipline to the children. When awe-awe is not the main income of the family, the mother does not put much control on their children about it. Awe-awe then become unique opportunities for the children to decide for themselves.